Adaptation of the Student Engagement Questionnaire (SEQ) into Indonesian Version for Secondary School Students - Diniyah, Usrotun; Hidayah, Nur; Hotifah, Yuliati (Indonesian Journal of Counseling and Development, 2025)
The goal of this research is to adapt the Student Engagement Questionnaire (SEQ) into the Indonesian version. The assessment that is adapted is the Student Engagement Questionnaire (SEQ) formulated by Reeve & Tseng, which consists of 22 items across four dimensions: agentic, behavior, emotion, and cognitive. The adaptation procedure follows the International Test Commission (ITC) Guidelines for Translating and Adapting Tests.  The sequence consists of six stages: (1) Initial development; (2) Test construction; (3) Validation; (4) Administration; (5) Scoring and interpreting; (6) Documentation phase. However, this study only reached the scoring and interpreting stage. Therefore, future researchers should continue similar studies through to the documentation stage. In this research, 2 translators, 2 psychometrics experts for content validation, 10 Islamic Junior High School students for readability assessments, and 385 Islamic Junior High School students for construct validation of the instrument are involved. The content validity test resulted in a total mean of 1.34 for the similarity aspect and 1.3 for the comparability aspect, with a s-CVI value of 1.00. The construct validity test, conducted using CFA, yielded results with CFI 0.931, TLI 0.922, RMSEA 0.062, and SRMR 0.045. Furthermore, the Cronbach's Alpha value was obtained at 0.94. Therefore, this instrument has been demonstrated to be both valid and reliable for assessing student engagement